George Washington - Abraham, Philip, 1970- (New York : Children's Press, 2002)
An easy-to-read biography of the first president of the United States.
Includes bibliographical references (p. 23) and index.
1.1
K-3
Keywords: Washington, George, -- 1732-1799 -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature; Washington, George, -- 1732-1799.; Presidents; Washington, George, -- 1732-1799.; Presidents -- United States -- Biography